Virtue Ethics and Meaning-Making in Shia Islamic Philosophy of Education: Implications for Teacher Professional Development - Hashemi, Zahrasadat (Iranian Journal of Educational Sociology, 2026)
Purpose: This study aims to develop and examine a Shia-informed conceptual framework that integrates virtue cultivation, meaning-making, and spiritual-ethical epistemology to strengthen teacher professional development and identity formation in contemporary educational contexts.Methods and Materials: A theoretical–conceptual design was employed, synthesizing key insights from Western virtue ethics and Shia Islamic educational philosophy to build an integrated model for teacher professional development. The study incorporated an illustrative qualitative case study at Farhangian University, Iran’s national teacher training institution. Twenty-five pre-service teachers participated in structured reflective workshops inspired by Philosophy for Children (P4C) and Shia epistemological principles, including Tawhid (unity and coherence of knowledge), Wilayah (ethical guardianship), and Imamate (knowledge-based leadership). Data were collected through observation of reflective dialogues and student narratives, analyzed thematically to identify how participants translated philosophical ideals into pedagogical reasoning and identity construction.Findings: Results indicate that integrating virtue ethics and Shia epistemology fosters deep moral reflection, professional coherence, and ethical agency among pre-service teachers. Participants demonstrated the ability to apply principles such as Tawhid to unify intellectual, moral, and spiritual domains; Wilayah to reframe classroom authority as compassion- and justice-based; and Imamate to embrace knowledge-based moral leadership. Engagement with these principles enhanced resilience, ethical decision-making, and meaning-making in the face of technological disruption and the changing epistemic role of teachers. The framework showed potential to enrich global discussions on virtue-based teacher development by incorporating transcendent and culturally resonant dimensions.Conclusion: This Shia-informed model bridges local educational philosophy with global virtue ethics discourse, offering an innovative pathway for rethinking teacher identity and moral formation in the AI era. It provides practical guidance for teacher training, curriculum design, and policy reform to integrate ethical and spiritual growth with pedagogical competence.